Constraints on dry season rice production in southeastern Cambodia - Chann Sinath; Tinsley, R.L.; Murty, V.V.N.; Demaine, Harvey; Hansen, G.K.; Swedish International Development Cooperation Agency (SIDA) (Bangkok : Asian Institute of Technology, 1996)
This study is related to the biological constraints on dry season flood recession rice in southeastern Cambodia. Its essential objectives are: (1) to study the yield gap between farm and on-farm experiment for rice production during dry season, (2) to evaluate the possible reason for the yield gap, (3) to determine the possible ways to eliminate the biological constraints in rice yield. The data in this study was collected from a field experiment, and farm interviews including crop cut. The experimental results show that the important contributor to the yield gap was fertilizer. But the fertilizer application without the pesticide application did not increase yield significantly, because insect damages play a second role in term of contribution to yield gap. There is no weed effect on yield gap because the experimental field was flood every year during the wet season. Yield was suppressed by severe rat damage. The result from the farm interview and crop cut survey show that the major factors of biological constraints were identified as rats, insects, diseases, and a few trouble weeds for the very early flood recession area. All the factors in biological constraint were rank by the farmers. The insects damage as the most important constraint, following by rats, diseases and weeds, respectively. The results from both experiment and farm interview and crop cut have the gap between the potential yield at the experimental field and at the actual farmer's practicing. This is because the experiment did not include rat control. Based on these results, the constraint experiment must include rodent control in the management package and survey must include more details about the problems are facing by the farmers.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1996
Keywords: Rice -- Cambodia